The implications of a graying Japan for government policy - R. Anton Braun; Douglas H. Joines (Federal Reserve Bank of Atlanta, 2014)
Japan is in the midst of a demographic transition that is both rapid and large by international standards. As recently as 1990, Japan had the youngest population among the Group of 6 large, developed countries. However, the combined effects of aging of the baby boomer generation and low fertility rates have produced very rapid aging. Japan now finds itself with the oldest population among the Group of 6, and its population will continue to age at a rapid pace in future years. Aging is already placing a burden on government finances, and Japan's ability to confront the negative fiscal implications of future aging is constrained by its very high debt-to-GDP ratio. We find that Japan faces a severe fiscal crisis if remedial action is not undertaken soon, and we analyze alternative strategies for correcting Japan's fiscal imbalances.
Keywords: E62; H51; H55; H63; 330; Japan; fiscal policy; aging; government